The whale : the true story of Luna - Parfit, Michael; Reynolds, Ryan.; Cedar Forest Films; Mountainside Films; New Video Group; Docurama (Firm) ([New York] : Docurama : New Video [distributor], 2012)
The Whale tells the remarkable true story of a young, wild killer whale (an Orca) nicknamed Luna, who lost contact with his family on the coast of British Columbia and became famous around the world when he tried to make friends with human beings
Title from container
Bonus features: Deleted scenes; Luna's birth drama; Exclusive interviews about Luna's family ; Four "Songs for Luna" music videos; Saving Luna trailer
Editor, Michael Parfit ; music, David Parfit, Tobin Stokes
Narrator, Ryan Reynolds
MPAA rating: G
DVD; Dolby digital, Stereo 5.1 surround
Keywords: Killer whale -- British Columbia -- Nootka Sound; Video recordings for the hearing impaired